Colloidal Zn3X2(X = P, As) quantum dots with metal salts and their transformation into (InyZn1-: Y )3X2via cation-exchange reactions - Baek, Seungmin; Ha, Jin Soo; Kim, Sungwoo; Kim, Sang Wook (Nanoscale, 2021)
We synthesized uniform Zn3X2 (X = P, As) quantum dots (QDs) for the first time using a stable, environmentally friendly zinc precursor instead of an organometallic precursor such as Me2Zn or Et2Zn, and controlled the QD size from about 2.0 nm to 6.0 nm. Moreover, tetragonal Zn3P2 and Zn3As2 QDs were transformed into zinc blende (InyZn1-y)3P2 and (InyZn1-y)3As2 QDs via the In3+ cationic-exchange reaction. To ensure the cation exchange reaction, we controlled reaction conditions, and confirmed it with various analytical methods. The replacement of Zn2+ by In3+ in the Zn3X2 QDs did not lead to changes in the particle size, but altered the optical properties and structure. In addition, we presented Cd3P2 and Cd3As2, which have the same tetragonal structure as the Zn3X2 QDs, through the same cationic exchange reaction.
Keywords: Analytical method; Cation exchange reactions; Cationic exchange reactions; Controlled reaction conditions; Organometallic precursors; Tetragonal structure; Zinc blende; Zinc precursor